2021
DOI: 10.1039/d1ra06314f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exopolysaccharide yield and antioxidant activities of Schizophyllum commune fermented products by the addition of Radix Puerariae

Abstract: To increase the production of exopolysaccharides and expand the application of Schizophyllum commune fermentation liquid, the traditional Chinese medicine Radix Puerariae with outstanding biological activity was selected as a culture additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…As shown in Table 1 , the total phenolics and total flavonoids of SC-RP were 3,731.56 ± 54.07 mg GAE/100 g, FW and 27.97 ± 0.41 mg CE/100 g, FW, respectively. SC-RP also contains 6.76 ± 0.47 mg/mL schizophyllan and 4.66 ± 0.05 mg/mL total protein ( 18 ). Moreover, the addition of RP introduces puerarin into the fermentation products, with a content of 56.45 ± 3.26 mg/100 g, FW.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Table 1 , the total phenolics and total flavonoids of SC-RP were 3,731.56 ± 54.07 mg GAE/100 g, FW and 27.97 ± 0.41 mg CE/100 g, FW, respectively. SC-RP also contains 6.76 ± 0.47 mg/mL schizophyllan and 4.66 ± 0.05 mg/mL total protein ( 18 ). Moreover, the addition of RP introduces puerarin into the fermentation products, with a content of 56.45 ± 3.26 mg/100 g, FW.…”
Section: Resultsmentioning
confidence: 99%
“…Radix Puerariae (RP) is rich in isoflavones, which are primary polyphenolic antioxidants found in medicinal and edible plants (16,17). Our previous study have confirmed that adding RP to the S. commune fermentation system can increase the antioxidant activity of the fermented supernatant, and these antioxidant activities are mainly contributed by the puerarin from RP and some new ingredients synthesized during fermentation such as resveratrol (18). Furthermore, the above results proves the feasibility of Schizophyllum liquid fermentation system as a bioreactor and provides a reference for the biotransformation of edible medicinal fungi such as Cordyceps militaris and Ganoderma lucidum et al…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations